(3GdcGaj JhVjM Md GdMGhjs - (3bWH GdOjf CMeO Hf GdMSf Hf CMeO GdZGdi GdTGaYjs; (3YHO GdZaGQ Hf YHO GdcQje Hf YHO GdZaGQ GdbRhjfj, fLe GdOjf,J (B665 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf ef GdCeQ GdhGVM CHjf ef adb GdaLQ GdehShe HGdMGhi GdefShH Edi LOi s
(3BNQgG (B:s
(3ef YUHJi (B,(3Gddg CYde s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B267s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B625s
Keywords: (3Gdabg GdTGaYjs